Analisis Kerusakan Crankshaft Terhadap Kinerja Auxiliary Engine Mitshubisihi 5DK 20 pada MV. Naziha - Samudra, Wahyu Ibnu; Darmana, Eka; Saleh, Agus (Politeknik Bumi Akpelni, 2025)
This study aims to analyze the factors causing crankshaft damage to the Mitsubishi 5DK-20 auxiliary engine on the MV Naziha. It also identifies the impact of the damage on the auxiliary engine performance and evaluates the maintenance system implemented on the ship. The research method used is descriptive qualitative, with data collection techniques through direct observation, field documentation, and interviews with engine room crew. This damage has a significant impact on the performance of the auxiliary engine, including decreased operational efficiency, increased vibration and abnormal noise, reduced ship electricity supply, and potential operational delays and shipping safety risks.The results of the study indicate that crankshaft damage on AE No. 3 is influenced by three main factors, namely: disruption of the lubrication system characterized by a decrease in oil pressure from 3 bar to a critical point of 1.2 bar so that the oil film layer is not formed perfectly; wear due to long-term operation, where the engine operates beyond 15,000 hours without bearing replacement according to manufacturer recommendations (12,000 hours); and weaknesses in the implementation of PMS (Plan Maintenance System) such as crankshaft deflection measurements and delayed bearing replacement due to tight operating schedules.